Life Cycle Analysis of Carbon Dioxide Emission Utilization in Enhanced Oil Recovery (EOR) Activity - Akhmad Hidayatno; Armand Omar Moeis; Achmad Yusaq Faiz Fadin (Indonesian Life Cycle Assessment Network (ILCAN), 2017)
The focus of this research is to analyze potential environmental impact in the utilization of carbon dioxide (CO2) as miscible gas injection on Enhanced Oil Recovery (EOR) activity. The reinjection of CO2 would reduce the amount of CO2 release in the air and is considered relatively as a new innovative approach. Responsible innovation (RI) is a research framework that considers aspects of sustainability both in terms of social, economic, and environmental toward an innovation made with five dimensions; reflexivity, deliberation, anticipation, responsiveness, and participation. However, RI does not have a specific quantitative approach to support the analysis. Therefore, this research proposes the use of simplified Life Cycle Assessment (LCA) as the quantitative analysis tool to support the RI analysis, using the case study of Subang Gas-Well, West Java, Indonesia. The case study has four main process units of CO2-Enhanced Oil Recovery, from the Well in Subang, CO2 Recovery, CO2 Transmission and the EOR Oil Well in Jatibarang. Based on the calculation, among the various impact categories, the biggest potential environmental impact is the contribution to acidification impact, followed by photo-oxidant formation, climate change and depletion of abiotic resources.